Coupling Reaction of Magnesium Alkylidene Carbenoids with α-Sulfonylallyllithiums: An Efficient Route to Multi-Substituted Vinylallenes - Kimura, Tsutomu; Kobayashi, Gen; Ishigaki, Masashi; Inumaru, Mio; Sakurada, Jo; Satoh, Tsuyoshi (Synthesis, 2012)
A variety of vinylallenes were successfully synthesized from 1-chlorovinyl p-tolyl sulfoxides and allyl or vinyl sulfones. Allyl and vinyl sulfones served as α-sulfonylallyllithium sources were prepared from carbonyl compounds in three or four steps in good overall yields. The coupling reaction of α-sulfonylallyllithiums with magnesium alkylidene carbenoids, which were generated from 1-chlorovinyl p-tolyl sulfoxides and isopropylmagnesium chloride, afforded multi-substituted vinylallenes in up to 88% yield.
Keywords: vinylallenes; magnesium alkylidene carbenoids; allyl sulfones; vinyl sulfones; 1-chlorovinyl p-tolyl sulfoxides; coupling